P101 A case of rare meningioangiomatosis associated with cortical dysplasia. (6th June 2017) - Gorgoglione, S; Pacilio, A; Manca, E; Petraccaro, A; Florio, L Di; Maggio, A; Spirito, A; Miglionico, L; Santis, R De; Ciliberti, A; Maruzzi, M; Ladogana, S; et al.
Abstract : Meningioangiomatosis(MA) is a rare malformative or hamartomatous lesion involved in meninges and cortex. Although it was originally described in association with NF-2, recent studies have revealed that it occurs more frequently in sporadic form. The pathogenesis remains unclear. MA has distinct histological and biological features to meningioma(M) but their association(MA-M) isn't unfrequent. Case report: a 12-years-old male was referred to our paediatric division for a history of headhache associated to malformative lesions shown at a first radiological investigation (CT and MRI) done in other hospital when he was 6 years old. At that time, neurosurgeons recommended follow up program. The lesions haven't change over the years, as shown at the follow-ups, however the persistence of headhache induced the family to request a second opinion. Our physical examination showed mental retardation. He had no family history or stigmata of NF2 and no seizure's history, electroencephalography didn't show anomalies. A head CT scan showed the presence of a right hyperdense single mass with gyriform signal pattern and clumped intralesional calcifications. MRI showed an intracranial mass measuring 2x3 × 2.5 cm located in the right posterior frontal cortex. The lesion was hyperintense on T2-weighted imaging and weakly hypointense on T1W1, with ring-like enhancement. MRI confirmed gyriform signal pattern associated to focal areas of cortical fronto-parietal dysplasia. The diagnosis of MA was made. Our patient didn't present seizure and the lesions appeared stable compared with the previous MRI so, in compliance with the neurosurgeon's advice, we established a long-term follow up program in association with symptomatic therapy for headhache. MA occurs mainly in children and younger adults with male predisposition, suffering from intractable seizure and less frequently headhache. Atypical symptoms included vomiting, diabetes insipidus, facial weakness, muscle atrophy and pain. MA is a single lesion usually stable or slowly growing. Imaging diagnoses for MA is difficult. The most common finding on CT is a round, single, hypodense mass with varying degrees of calcification. On MRI, the lesions seem confined to the cortex. On T1WI, MA shows a low or iso-intense signal, on T2WI lesions are more frequently hyperintense, but sometimes they can be hypointense. A gyriform signal pattern is common on either CT or MRI, typical of sporadic MA and it's helpful to distinguish pure MA from MA-M.